2016
DOI: 10.1111/his.12956
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia in Barrett's oesophagus: p53 immunostaining is more reproducible than haematoxylin and eosin diagnosis and improves overall reliability, while grading is poorly reproducible

Abstract: p53 immunohistochemistry interpretation is more reliable than dysplasia diagnosis, even with limited training. As it is predictive of prognosis and improves diagnostic reproducibility, it is suitable for routine use by pathologists as an adjunct to dysplasia diagnosis. The distinction of LGD versus HGD was poor. This study supports simplifying dysplasia diagnosis into 'present', 'indefinite' or 'absent', and the use of p53 as an ancillary marker in difficult cases. This should help to prevent overdiagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…In dysplastic Barrett’s epithelium in humans, upregulation of p53 staining is often considered one of the main characteristics of high-grade dysplasia 24, 25, 26, 27, 28. p53 was positive in all of the dysplastic legions, 12/15 (80%) metaplasias in the EGJ model, and 1/6 (16.7%) metaplasia in the EJ/TG model (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In dysplastic Barrett’s epithelium in humans, upregulation of p53 staining is often considered one of the main characteristics of high-grade dysplasia 24, 25, 26, 27, 28. p53 was positive in all of the dysplastic legions, 12/15 (80%) metaplasias in the EGJ model, and 1/6 (16.7%) metaplasia in the EJ/TG model (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The columnar mucosal regions seem to represent true metaplastic lineages because they demonstrate characteristics distinct from jejunal mucosa including expression of the duodenal transcription factor PDX-1. It is also notable that more dysplastic lesions showed increased nuclear p53 staining, a hallmark of high-grade dysplasia in human Barrett’s esophagus 24, 25, 26, 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…The first study showed improvement in interobserver weighted κ scores after addition of p53 IHC, from 0.42 to 0.48 (both ‘moderate’) . The second study investigated the generalisability of p53 IHC, and showed that p53 IHC interpretation was more reliable than HE interpretation for diagnosing BO + dysplasia cases, and improved the mean interobserver weighted κ score from 0.47 to 0.55 (both ‘moderate’) . Both studies also showed aberrant p53 expression to be an independent predictor of disease progression.…”
Section: Discussionmentioning
confidence: 96%
“…performed two histopathological studies to investigate the added value of p53 IHC on observer agreement among two groups of pathologists. The first study consisted of a group of five pathologists assessing 186 single‐slide cases of BO, and the second study consisted of a group of 10 pathologists assessing 72 BO cases . The first study showed improvement in interobserver weighted κ scores after addition of p53 IHC, from 0.42 to 0.48 (both ‘moderate’) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation